2019
DOI: 10.1634/theoncologist.2019-0297
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Study of Combination Therapy with MEK Inhibitor Binimetinib and Phosphatidylinositol 3-Kinase Inhibitor Buparlisib in Patients with Advanced Solid Tumors withRAS/RAFAlterations

Abstract: Background This multicenter, open‐label, phase Ib study investigated the safety and efficacy of binimetinib (MEK inhibitor) in combination with buparlisib (phosphatidylinositol 3‐kinase [PI3K] inhibitor) in patients with advanced solid tumors with RAS/RAF alterations. Materials and Methods Eighty‐nine patients were enrolled in the study. Eligible patients had advanced solid tumors with disease progression after standard therapy and/or for which no standard therapy existed. Evaluable disease was mandatory, per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Although not currently specific to patients with prostate cancer, clinical trials exploring co-inhibition of the PI3K-AKT-mTOR and MAPK cascades to treat various advanced solid cancers have also been developed (e.g., ClinicalTrials.gov identifiers: NCT01390818, NCT01347866, and NCT02583542), although response rates appear to be low and are linked to RAS and RAF mutations [ 277 ]. For example, a recent Phase Ib study of combination therapy with the MEK1/2 inhibitor binimetinib (Mektovi) and the pan-PI3K inhibitor Buparlisib (BKM120) in advanced solid tumors reported promising efficacy in patients with advanced ovarian cancer with RAS / RAF genetic alterations, however continuous dosing resulted in intolerable toxicities and an intermittent schedule is suggested for future trials [ 278 ]. Additionally, the MATCH screening trial (targeted therapy directed by genetic testing in treating patients with advanced refractory solid tumors, lymphomas, or multiple myeloma, ClinicalTrials.gov identifier: NCT02465060) will investigate the efficacy of MEK and PI3K inhibitors as monotherapies in patients with progressive disease that carries a genetic alteration in either the RAS/MAPK or the PI3K-AKT-mTOR pathways respectively.…”
Section: The Pi3k-akt-mtor Pathway Intersects With Multiple Oncogementioning
confidence: 99%
“…Although not currently specific to patients with prostate cancer, clinical trials exploring co-inhibition of the PI3K-AKT-mTOR and MAPK cascades to treat various advanced solid cancers have also been developed (e.g., ClinicalTrials.gov identifiers: NCT01390818, NCT01347866, and NCT02583542), although response rates appear to be low and are linked to RAS and RAF mutations [ 277 ]. For example, a recent Phase Ib study of combination therapy with the MEK1/2 inhibitor binimetinib (Mektovi) and the pan-PI3K inhibitor Buparlisib (BKM120) in advanced solid tumors reported promising efficacy in patients with advanced ovarian cancer with RAS / RAF genetic alterations, however continuous dosing resulted in intolerable toxicities and an intermittent schedule is suggested for future trials [ 278 ]. Additionally, the MATCH screening trial (targeted therapy directed by genetic testing in treating patients with advanced refractory solid tumors, lymphomas, or multiple myeloma, ClinicalTrials.gov identifier: NCT02465060) will investigate the efficacy of MEK and PI3K inhibitors as monotherapies in patients with progressive disease that carries a genetic alteration in either the RAS/MAPK or the PI3K-AKT-mTOR pathways respectively.…”
Section: The Pi3k-akt-mtor Pathway Intersects With Multiple Oncogementioning
confidence: 99%
“…These results have led to a number of clinical trials combining PI3K pathway inhibitors with MEKi across a variety of cancers. Many of these studies have found an initial positive tumor response with cancers responding better than monotherapy alone, but these studies have run into issues regarding dose toxicity for longer-term treatment [84][85][86]. Similarly, studies targeting the Hippo pathway through YAP inhibition after MEKi treatment showed positive results in BRAF-mutant tumor cell lines, and combination treatment was able to overcome acquired resistance to MEKi [64].…”
Section: Targeting Parallel Pathwaysmentioning
confidence: 99%
“…4,5 Mutations in KRAS constitutively activate its downstream signaling pathways 6 such as MEK/ERK, a mitogen-activated protein kinase (MAPK) pathway, this is known to promote cancer cell survival and chemoresistance. 7,8 KRAS mutations correlate significantly to poor therapeutic response in NSCLC patients. [9][10][11] Therefore, it is essential to develop novel KRAS-targeting drugs for treating recalcitrant NSCLC patients with KRAS mutations.…”
Section: Introductionmentioning
confidence: 99%